Cytocompatible Drug Delivery Hydrogels Based on Carboxymethylagarose/Chitosan Ph-Responsive Polyelectrolyte Complexes - Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B; Ortiz-Nunez, J; Zapata-Ramirez, P (Elsevier B.V., 2022)
Several drugs are chemically unstable in the gastric environment and have low bioavailability restricted by intestinal absorption, which motivates the development of alternative routes for drug release, such as transdermal drug carriers for drug delivery to specific areas of the skin. Herein, novel polyelectrolyte complexes (PEC) consisting of carboxymethylagarose (CMA) and chitosan (CS) were prepared. pH-responsive CMA/CS hydrogels were obtained by mixing CMA and CS at various weight ratios. Swelling ratio was modulated by varying the CMA and CS weight ratio, and the highest swelling values were achieved for 2:1 wt% hydrogels at 25 °C and pH 6.0. PEC films were characterized by ATR-FTIR spectroscopy, TGA, DSC, and SEM. Results indicated that CMA and CS were successfully crosslinked by ionic complexation. As a model drug, diclofenac sodium (DS) was loaded in CMA/CS PECs. Association efficiency and loading capacity were ca. 69% and 79%, respectively, exhibiting 67% cumulative release after 72 h at 37 °C and pH 6.0 through Fickian diffusion mechanism. Viability assay of immortalized human keratinocyte (HaCat) cells showed ca. 100% survival in the presence of hydrogels and DS. Therefore, this work suggests that CMA/CS PECs can be applied as pH-responsive carriers for dermal drug delivery. © 2021 Elsevier B.V.